Clinical efficacy of antibiotic-loaded bone cement and negative pressure wound therapy in multidrug-resistant organisms diabetic foot ulcers: a retrospective analysis - Guo, Huihui; Xue, Zhenqiang; Mei, Siwei; Li, Tengfei; Yu, Haiyang; Ning, Tao; Fu, Yongbin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThe purpose of this study was to investigate the clinical efficacy of antibiotic-loaded bone cement (ALBC) combined with Negative pressure wound therapy (NPWT) aspiration technique in the treatment of multidrug-resistant diabetic foot ulcers (MDRO-DFUs).MethodsA retrospective analysis of the clinical data of 80 patients with MDROs-DFU who were used Vacuum sealing drainage (VSD) as NPWT excipient and met the inclusion criteria from January 2019 to January 2024 at our hospital. Patients were divided into an experimental group and a control group, with 40 cases in each. The control group received conventional treatment, routine debridement, and NPWT treatment, while the experimental group received ALBC treatment in addition to the treatment plan of the control group. Measurements of blood inflammatory indicators, foot hemodynamic indicators, wound bacterial clearance time, wound healing time, and hospital stay were taken before and after treatment for both groups.ResultsInflammatory indexes, Vascular endothelial growth factor(VEGF), and internal diameter of dorsalis pedis arteriosus of both groups after treatment were significantly better than those before treatment, and the improvement of the experimental group was more obvious than that of the control group; the experimental group had a significantly shorter time of trauma bacterial turnover, healing time of trauma, and hospitalization time compared with that of the control group (P<0.05).